Mental health, substance addiction and mortality risk among people in prison - Cooper, Janine; Ross, Emma; Maguire, Aideen; O’Reilly, Dermot; Kirk, Richard; Kelly, Trish; McGarrigle, Stephen; Gray, Ruth; Cardwell, Christopher; Murphy, Siobhán; Donnelly, Michael (International Journal of Population Data Science, 2025)
People in prison often have a complex mix of health and care needs and face an increased mortality risk after release. Objectives: (i) examine mental health and substance addiction in the Northern Ireland prison population; (ii) examine mortality after prison release; (iii) characterise who is most at-risk of death post-release. The project used prison healthcare data (adults entering prison, January 2012-December 2021) linked to a healthcare population spine, income deprivation data and mortality data in the Honest Broker Service to examine a range of outcomes. Substance addiction - logistic regression was used to examine self-reported substance addiction and subsequent self-harm, crisis management support, and use of mental health services in prison. Mortality after prison release (analyses underway) - cox proportional hazards models will be used to examine the risk of suicide, drug-related death, death by external causes, and all-cause mortality in individuals released from prison compared to the general population. The study population consisted of 2,746 individuals; this was largely younger males. Over two-fifths of individuals reported an addiction to drugs and/or alcohol at entry into prison (42%; n=1,153). In prison, self-harm was recorded among 7.9% of individuals (n=216); over one in five received crisis management support (20.6%; n=566) and over one in ten used mental health services (11.5%; n=315). Individuals with reported drug and/or alcohol addiction at entry into prison were more likely to present with self-harm [adjusted odds ratio (aOR) 1.85 (95%CI 1.37-2.50)], require crisis management support [aOR 1.85 (95%CI 1.52-2.25)] and use mental health services in prison [aOR 2.10 (95%CI 1.63-2.69)] compared to individuals with no addiction. We also plan to present preliminary results examining mortality risk after release. The Northern Ireland prison population has significant health needs, particularly in relation to substance addiction. Resources are required to address these concerns/unmet healthcare needs in this population. Data for this project was provided by the HSC Honest Broker Service; any views or opinions presented are solely those of the author.